Image analysis of 4D MRI images for improved radiotherapy of lung cancer patients. - Teng, Serene Shu Hui. (2012)
Effective radiotherapy planning (RTP) for lungs cancer treatment required maximum soft tissue image contrast and this can be achieved by using magnetic resonance imaging (MRI). In recent years, interest has been grown in the development of RTP techniques based solely on MR images. In addition, research has been carried out to expand the use of MRI to the detection of movement which can be included in the RTP process. This technique of using MRI to detection of movement is known as dynamic MRI (4DMRI).